2015
DOI: 10.1371/journal.pone.0122657
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Cdx-2 Polymorphism and Premenopausal Breast Cancer Risk in Southern Pakistani Patients

Abstract: BackgroundVitamin D3 is a secoster oid that exerts its effect by binding to its nuclear receptor called vitamin D receptor (VDR), inducing apoptosis and thereby inhibiting cell proliferation in cancer cells. The VDR receptor, located in the nucleus, is known to regulate the functions of over 200 genes. Various allelic forms of hVDR have been discovered that increase susceptibility to various cancers. The VDR-Cdx2 polymorphism, located in the promoter region of exon 1e in the VDR gene, influences the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 64 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…Dietary factors associated with increased BC risk included intake of total n-6 polyunsaturated fatty acids (PUFA) (Kiyabu et al, 2015), vitamin D deficiency or insufficiency (Shi et al, 2014a;Park et al, 2015a), high levels of serum cadmium (Nagata et al, 2013;Itoh et al, 2014;Ding et al, 2015), high intake of salt (Park et al, 2014b), sugar (Sulaiman et al, 2014), meat (Ko et al, 2013), and saturated fat and oils (Balasubramaniam et al, 2013;Wang et al, 2013a). In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Dietary factors associated with increased BC risk included intake of total n-6 polyunsaturated fatty acids (PUFA) (Kiyabu et al, 2015), vitamin D deficiency or insufficiency (Shi et al, 2014a;Park et al, 2015a), high levels of serum cadmium (Nagata et al, 2013;Itoh et al, 2014;Ding et al, 2015), high intake of salt (Park et al, 2014b), sugar (Sulaiman et al, 2014), meat (Ko et al, 2013), and saturated fat and oils (Balasubramaniam et al, 2013;Wang et al, 2013a). In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Similarly, various casecontrol studies suggested that the association between VDR polymorphism and risk of breast cancer may depend on race and ethnicity. Furthermore, these studies also showed inconsistent results, some suggesting the association of VDR polymorphism with breast cancer, while others suggested a lack of association (3,19,(24)(25)(26)(27)(28)(29)(30)(31). No association between VDR polymorphisms and breast cancer risk was found, however, modification of this relationship was observed with the menopausal status in Europeans (VDR rs4328262 and rs11168292) and East Asians (VDR rs11168287).…”
Section: Female Reproductive Tract Cancermentioning
confidence: 99%
“…VDR gene polymorphism is associated with the breast cancer risk [117][118][119][120][121][122][123][124][125] but insufficient data are available to find the relationship with breast cancer risk [126]. The studies have pointed out allelic variations in VDR gene, such as Cdx2, Fok1, Bsm1, Taq1, Apa1 and Poly A in different ethnic groups with breast cancer incidence with contradictory results [117,118,121,126].…”
Section: Vdr Gene Polymorphisms and Breast Cancermentioning
confidence: 99%
“…The studies have pointed out allelic variations in VDR gene, such as Cdx2, Fok1, Bsm1, Taq1, Apa1 and Poly A in different ethnic groups with breast cancer incidence with contradictory results [117,118,121,126].…”
Section: Vdr Gene Polymorphisms and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation